PERAN KELUARGA SEBAGAI CAREGIVER TERHADAP PENINGKATAN KUALITAS HIDUP LANSIA - Tulangow, Natasya Syalom; Ake, Julianus; Laka, Angela (Lasalle Health Journal, 2024)
Introduction: Elderly people experience a decline in physiological and psychological functions, which can have an impact on physical weakness, helplessness, feelings of worthlessness, from changes experienced by the elderly, can cause unhappiness and affect their quality of life. The quality of life of the elderly is related to the welfare of the elderly because it can be assessed from the health of physical and psychological conditions. The role of the family as a caregiver can have a positive impact on the quality of life of the elderly. Objective: To analyze the role of the family as a caregiver in improving the quality of life of the elderly. Method: This study used a cross-sectional approach, with a population of 80 elderly respondents and a sampling technique of 80 respondents. Results: Based on data analysis using the Spearman rho test, the results showed that there was a significant relationship between the role of the family as a caregiver in improving the quality of life of the elderly. Conclusion: There is a relationship between the role of the family as a caregiver and improving the quality of life of the elderly. Thus, the better the role of the family, the better the quality of life of the elderly